Understanding the Goals of Service Learning and Community-Based Medical Education: A Systematic Review: Service Learning in Medical Education - Khan, Marina; Waqar, Hanzala; Pervez, Farida; Zahid, Palwasha; Khan, Muhammad Abbas; Fatima, Syeda Sanaa (Pakistan Journal of Health Sciences, 2025)
Service learning (SL) and community-based medical education (CBME) are increasingly integrated into undergraduate medical training to prepare students for socially accountable practice. While many programs report benefits for students and communities, the specific goals emphasized across contexts remain inconsistently defined. Objectives: To provide a comprehensive understanding of how SL and CBME contribute not only to student learning but also to community engagement and institutional development. Methods: Following the PRISMA 2020 guidelines, PubMed, Scopus, and the Cochrane Library were searched for English-language studies published between 2019 and 2024. Eligible studies included those involving undergraduate medical students participating in SL or CBME interventions. Data on study design, participants, interventions, and reported outcomes were extracted. Quality appraisal was conducted using the CASP, MMAT, and JBI tools. A thematic synthesis approach was used to categorize findings into educational, community, and institutional domains. Results: Sixteen studies were included, spanning Africa, Asia, North America, and the Middle East. Most studies reported educational outcomes such as improved clinical competence, empathy, reflective capacity, and professional identity formation. Community-level goals included increased access to care, health promotion, and stronger partnerships. Institutional goals, such as enhancing curricular relevance and social accountability, were less frequently documented. Few studies evaluated long-term sustainability or objectively measured community outcomes. Conclusions: SL and CBME consistently promote student growth while fostering community engagement. However, systematic evaluation of institutional impact and program sustainability remains limited. Future research should adopt longitudinal, multi-institutional approaches to capture durable outcomes and guide curricular reforms aligned with social accountability.